Quality of government and the relationship between natural disasters and child poverty: A comparative analysis - Adel Daoud; Björn Halleröd; Debarati Guha Sapir (Max Planck Institute for the Study of Societies, 2015)
This paper explores the degree to which exposure to reoccurring natural disasters of various kinds explains seven dimensions of severe child poverty in 67 middle- and low-income countries. It also analyzes how certain institutional conditions, namely the quality of government (QoG), have moderating effects on the relationship between disasters and child poverty. Two main hypotheses are tested. The first is that disasters do have an adverse average effect on severe poverty. The second is that disasters reveal a positive coefficient (i.e., more disasters, more deprivation) but that higher levels of QoG negatively moderate this effect, i.e., the adverse effect of disasters is diminished by increasingly high QoG levels. From 70 possible combinations of relationships (7 types of deprivation combined with 10 types of natural disaster measures), 11 have the expected correlation between disasters and child deprivation and only one has the expected interactive correlation between quality of government, disasters, and child poverty. Several unexpected results could also be observed which are discussed in the paper along with recommendations for future research. – – Das Papier untersucht den Zusammenhang zwischen hoher Kinderarmut und Ausmaß und Häufigkeit von Naturkatastrophen. Hierzu werden sieben Dimensionen der Kinderarmut in 67 Ländern mit mittlerem und niedrigem Pro-Kopf-Einkommen analysiert, die wiederholt von Naturkatastrophen betroffen sind. Am Beispiel der Regierungsqualität (Quality of Government, QoG) wird weiterhin untersucht, ob und inwieweit institutionelle Rahmenbedingungen den Zusammenhang zwischen Katastrophen und Kinderarmut beeinflussen. Zwei Haupthypothesen werden getestet: (1) Katastrophen haben generell einen negativen Effekt auf schwere Armut; (2) Katastrophen haben einen positiven Koeffizienten (mehr Katastrophen, mehr Deprivation), aber höhere QoG-Werte mildern diesen Effekt, das heißt, die negativen Auswirkungen von Katastrophen werden von höheren QoG-Werten abgeschwächt. Von siebzig möglichen Beziehungskombinationen (sieben Deprivationstypen kombiniert mit zehn Schweregraden von Naturkatastrophen) weisen elf die erwartete Korrelation zwischen Katastrophen und Deprivation bei Kindern auf, aber nur eine besitzt die erwartete interaktive Korrelation zwischen QoG, Katastrophen und Kinderarmut. In dem Discussion Paper werden darüber hinaus verschiedene unerwartete Ergebnisse sowie Empfehlungen für die weitere Forschung diskutiert.
Keywords: 300